2010
DOI: 10.1590/s1413-81232010000700061
|View full text |Cite
|
Sign up to set email alerts
|

Perfil e práticas de saúde bucal do agente comunitário de saúde em municípios piauienses de pequeno porte

Abstract: Perfil e práticas de saúde bucal do agente comunitário de saúde em municípios piauienses de pequeno porteProfile and procedures of the community health agents regarding oral health in the countryside of Piauí State, Brazil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
36

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 9 publications
1
7
0
36
Order By: Relevance
“…This is the same condition observed by Mialhe et al 15 , Moura et al 29 , who confirmed that the community health agents did not have any training or preparation to conduct educational activities in oral health.…”
Section: III -Guidelines Offered To the Community About Oral Healtsupporting
confidence: 88%
See 3 more Smart Citations
“…This is the same condition observed by Mialhe et al 15 , Moura et al 29 , who confirmed that the community health agents did not have any training or preparation to conduct educational activities in oral health.…”
Section: III -Guidelines Offered To the Community About Oral Healtsupporting
confidence: 88%
“…Mialhe et al 15 , Moura et al 29 confirmed that the CHA knowledge about oral health was constructed and grounded in educational activities performed by dentists from the public network in the health unit or from school programs.…”
Section: III -Guidelines Offered To the Community About Oral Healtmentioning
confidence: 98%
See 2 more Smart Citations
“…Por outro lado, os agentes mais jovens não conhecem tão bem a comunidade e seu envolvimento pode ser menor, entretanto, seus conceitos de saúde e doença podem não ser muito aprofundados, estando mais abertos às transformações. (MOURA et al, 2010) Nesse grupo profissional, as jornadas de trabalho podem levar ao cansaço físico, mental e ao desgaste emocional podendo acarretar doenças referentes ao estresse (MESQUITA; MOREIRA; NETO, 2013), o que é bem evidenciado, pois somente 14,29% dos ACS apresentam outro emprego.…”
Section: Análise E Discussãounclassified